Peran Gereja dalam Misi - Mintoni Asmo Tobing (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2019)
Abstract: Church is an institution that is established by God in the world with a purpose, that the church does its duty. But in reality, a lot of churches are not functioning as church anymore, because they are trapped with many activities that have no connection with the duty of the church itself. The duty of the church is ignored, but some activities that look like the duty are many. This article contains of the contemporary church’s problems, designed with a purpose to bring the identity of the church, so that the church goes back to its function. Church is sent by God to the world with a purpose as the instrument of God’s mission, so the church, its function and activities must return to the original calling of the church.